COVID‐19 and myasthenia gravis: A review of neurological implications of the SARS‐COV‐2. Issue 12 (28th October 2022) - Shah, Syed Muhammad Ismail; Yasmin, Farah; Memon, Roha Saeed; Jatoi, Nadia Nazir; Savul, Ilma Saleh; Kazmi, Sana; Monawwer, Syed Abdullah; Zafar, Muhammad Daim Bin; Asghar, Muhammad Sohaib; Tahir, Muhammad Junaid; Lee, Ka Yiu
Abstract: Introduction: This review highlights the potential mechanisms of neuromuscular manifestation of COVID‐19, especially myasthenia gravis (MG). Methods: An extensive literature search was conducted by two independent investigators using PubMed/MEDLINE and Google Scholar from its inception to December 2020. Results: Exacerbations of clinical symptoms in patients of MG who were treated with some commonly used COVID‐19 drugs has been reported, with updated recommendations of management of symptoms of neuromuscular disorders. Severe acute respiratory syndrome coronavirus 2 can induce the immune response to trigger autoimmune neurological disorders. Conclusions: Further clinical studies are warranted to indicate and rather confirm if MG in the setting of COVID‐19 can pre‐existent subclinically or develop as a new‐onset disease.